MENINGKATKAN KESADARAN PEREMPUAN KATOLIK TERHADAP KELOMPOK DOA SERIKAT SANTA ANNA DAN IMPLIKASINYA BAGI PENGHAYATAN IMAN DALAM KEHIDUPAN MENGGEREJA DI STASI SANTO MIKHAEL ASUEMAN PAROKI SANTO THEODORUS WELULI - Dasi, Adelia Elma Lawa; Amsikan, Modesta; Binsasi, Frederikus (JURNAL PROPHETA, 2025)
God created human in His own image and likeness. Indirectly, God also created humanity to live in fellowship. In daily life, people increasingly recognize the importance of togetherness as a community in strengthening their faith. Women also actively participate in spiritual organizations to deepen their faith. This role is evident among Catholic women at St. Michael's Station, Asueman – under the Parish of St. Theodorus Weluli. One such spiritual fellowship is the prayer group called the Society of Saint Anna. However, many Catholic women—especially those who are newly married—tend to lack awareness or willingness to join this prayer group. This is due to various reasons such as lack of free time, restrictions from their husbands, and other personal circumstances. The purpose of this thesis is to examine the need for Catholic women to increase their awareness and participation in the Society of Saint Anna prayer group, and to understand the role this group plays in deepening the faith of Catholic women within the life of the Church. The research method used is a qualitative approach, specifically a descriptive qualitative study. Data sources include Catholic women who are not yet involved in any spiritual organization, current members of the Society of Saint Anna, the parish priest of St. Theodorus Weluli, and the head of St. Michael's Station, Asueman. The results of the data analysis indicate that Catholic women in the Parish of St. Theodorus Weluli – St. Michael's Station, Asueman, recognize that the Society of Saint Anna is a valuable spiritual organization for strengthening the faith of its members. However, due to their roles as wives and mothers, many Catholic women still do not have the proper opportunity to join such a group. Nevertheless, they strive to live according to the teachings of the Catholic Church in their daily lives.